EDUKASI DIIT YANG TEPAT UNTUK PENGENDALIAN PENYAKIT TIDAK MENULAR PADA LANSIA DI DESA NARMADA LOMBOK BARAT - Dewi Nur Sukma Purqoti; Zaenal Arifin; Dian Istiana; Baiq Rulli Fatmawati; Ilham; Zuliardi (CV. ALIM'SPUBLISHING, 2024)
Non-communicable diseases (NCDs) are currently the biggest cause of death. According to WHO, NCDs are the leading cause of death in the world, where in 2016 as many as 71% of deaths were caused by non-communicable diseases. Based on the type of disease causes of death include cardiovascular disease (31%), cancer (16%), chronic respiratory disease (7%) and diabetes mellitus (3%).WHO data also shows that the mortality rate due to non-communicable diseases in the Southeast Asian region is quite high, which is around 23% when compared to European countries (17%) and America (15%), proper control of diit can reduce the incidence of NCDs. Method: This method of community service is carried out in the form of providing education about the right diit for non-communicable disease control by means of lectures and distributing leflets followed by questions and answers and discussion. Conclusion: from the results of the service, it can be concluded that the education provided can increase public knowledge about non-communicable diseases, so that the community is expected to be able to prevent and handle NCDs themselves with the right diit arrangements